Zakat, Infaq, and Sedekah (ZIS) Management in Economic Recovery in Makassar Indonesia: A Cross-Cultural Perspective from Turkey and Egypt - Nur Saidy, Emily; Mahsyar, Nun Maziyah; Ashraf, Amal (BANCO: Jurnal Manajemen dan Perbankan Syariah, 2025)
Purpose – This study examined the distribution and effectiveness of ZIS (Zakat, Infak, and Sedekah) funds in facilitating economic recovery via a comparative examination of Turkey and Egypt. This research situates Islamic social finance within the maqāṣid al-sharī‘ah paradigm, with a specific emphasis on ḥifẓ al-māl (protection of wealth) and ḥifẓ al-nafs (protection of life), illustrating the role of religious generosity in enhancing resilience and well-being in post-crisis scenarios. Method – Employing a qualitative phenomenological approach, this research explores the lived experiences of stakeholders while drawing comparisons with the zakat systems implemented in Egypt and Turkey. Findings – The study reveals that, while ZIS distribution in Makassar has positively impacted many beneficiaries, its effectiveness in fostering sustainable economic growth remains constrained by limited funding and a lack of capacity-building programs. Lessons from Egypt and Turkey offer actionable insights for improving the ZIS system in Makassar. Practical Implications – This study theoretically enhances the discussion on Islamic social finance by connecting ZIS to global sustainability initiatives, including the SDGs (No Poverty, Reduced Inequalities, and Decent Work and Economic Growth). The comparative viewpoint offers valuable insights for policymakers and financial institutions seeking to develop inclusive recovery policies that incorporate religious and cultural values. Originality/Value – By adopting a comparative and cross-cultural approach, this study provides unique insights into the distribution and effectiveness of ZIS funds in a post-pandemic context, thereby contributing to the broader discourse on improving the zakat system